A numerical corrosion-fatigue model for biodegradable Mg alloy stents. (1st October 2019) - Shen, Zhenquan; Zhao, Ming; Zhou, Xiaochen; Yang, Hongtao; Liu, Jianing; Guo, Hui; Zheng, Yufeng; Yang, Jian-An
Graphical abstract: Abstract: Biodegradable magnesium alloys have attracted research interest as matrix materials for next-generation absorbable metallic coronary stents. Subject to cyclic stresses, magnesium alloy stents (MAS) are prone to premature failures caused by corrosion fatigue damage. This work aimed to develop a numerical continuum damage mechanics model, implemented with the finite element method, which can account for the corrosion fatigue of Mg alloys and the applications in coronary stents. The parameters in the resulting phenomenological model were calibrated using our previous experimental data of HP-Mg and WE43 alloy and then applied in assessing the performance of the MAS. The results indicated that it was valid to predict the degradation rate, the damage-induced reduction of the radial stiffness, and the critical location of the MAS. Furthermore, this model and the numerical procedure can be easily adapted for other biodegradable alloy systems, for instance, Fe and Zn, and used to achieve the optimal degradation rate while improving fatigue endurance. Statement of Significance: Subject to cyclic stresses, magnesium alloy stents are prone to premature failures caused by corrosion fatigue damage. This work aimed to develop a numerical continuum damage mechanics model, implemented with the finite element method, which can account for the corrosion fatigue of Mg alloys and the applications in coronary stents. The results indicated that it was valid to predict the degradation rate, damage-induced reduction of the radial stiffness, and the critical location of the Mg alloy stent; therefore, these stents can be easily adapted to other biodegradable alloy systems such as Fe and Zn.